2018
DOI: 10.3390/nu10101399
|View full text |Cite
|
Sign up to set email alerts
|

A Water-Soluble Extract from Actinidia arguta Ameliorates Psoriasis-Like Skin Inflammation in Mice by Inhibition of Neutrophil Infiltration

Abstract: Psoriasis is a chronic inflammatory disease with complex etiology involving multiple factors. Current treatment methods are highly limited and there is a strong need for the development of safer and efficacious agents. We have previously shown that a water-soluble extract derived from hardy kiwifruit Actinidia arguta, called PG102, shows potent anti-inflammatory effects. Based on its reported biological activities, the effects of PG102 were examined on imiquimod-induced psoriasis-like skin inflammation. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…PG102 is a standardized extract from an edible portion of Actinidia arguta . It has been shown to alleviate clinical symptoms of various animal disease models including spontaneous dermatitis, atopic dermatitis, and psoriasis-like skin inflammation [1315]. Furthermore, an exploratory human clinical study with 90 asymptomatic atopy patients (serum total IgE > 300 IU/mL) has verified significant immunomodulatory effects along with the safety of PG102 [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PG102 is a standardized extract from an edible portion of Actinidia arguta . It has been shown to alleviate clinical symptoms of various animal disease models including spontaneous dermatitis, atopic dermatitis, and psoriasis-like skin inflammation [1315]. Furthermore, an exploratory human clinical study with 90 asymptomatic atopy patients (serum total IgE > 300 IU/mL) has verified significant immunomodulatory effects along with the safety of PG102 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an exploratory human clinical study with 90 asymptomatic atopy patients (serum total IgE > 300 IU/mL) has verified significant immunomodulatory effects along with the safety of PG102 [16]. Recently, we have reported that PG102 suppresses the expression of AMPs in HaCaT cells stimulated with inflammatory cytokines [15].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the crosstalk between skin‐resident keratinocytes and innate immune cells generates inflammatory and immune circuits responsible for the initiation, progression and persistence of the disease . In psoriatic lesions, the antimicrobial peptide LL‐37 produced by keratinocytes combined with self‐DNA released from injured cells activates dendritic cells and T cells, and subsequently leads to the production of IL‐23, IL‐17A and IL‐22 and the activation of keratinocytes . The activated keratinocytes secrete pro‐inflammatory cytokines and chemokines, leading to the recruitment of neutrophils to the lesional skin .…”
Section: Introductionmentioning
confidence: 99%
“…The activated keratinocytes secrete pro‐inflammatory cytokines and chemokines, leading to the recruitment of neutrophils to the lesional skin . The infiltrated neutrophils can secrete pro‐inflammatory cytokines and form neutrophil extracellular traps (NETs), consequently exacerbating the disease progression . Therefore, the evolving knowledge of the role of innate immunity and the cell‐cell communication in psoriasis has had a significant impact on revealing the mechanism of the pathogenesis of psoriasis and developing new therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…HaCaT cells are immortalized cells, which are commonly used in the studies relevant to psoriasis (13). To mimic conditions of psoriatic keratinocytes, HaCaT cells were induced with M5 (consisting of IL-17A, IL-22, IL-1alpha, TNF-alpha and Oncostatin M) as previous reported (27). Therefore, we established a cell model of highly proliferative psoriatic keratinocytes via treating HaCaT cells by M5.…”
mentioning
confidence: 99%